Dampak Penurunan Aktivitas Wisata Terhadap Keseimbangan Ekosistem Miga Beach,Gunungsitoli - Laia, Maestro (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the impact of decreased tourism activities on ecosystem balance at Miga Beach, Gunungsitoli. The method used is descriptive qualitative through direct observation in the field. The results show that the decline in tourist visits has a two-way impact. On the one hand, pressure on the environment such as pollution and disturbances to flora and fauna decreased. However, on the other hand, there is damage to facilities, illegal logging, and increased waste due to the lack of supervision and conservation.